The ostensible tension between competition and cooperation in ports: A case study on intra-port competition and inter-organizational relations in the Rotterdam container handling sector - Bob Castelein; Harry Geerlings; J. H. R. van Duin (Journal of Shipping and Trade (JST), 2019)
Strategic alliances in the container shipping sector, and requirements imposed by consolidated hinterland modalities such as trains and barges, have resulted in container terminals facing increasing pressures to cooperate to handle increasingly intertwined container flows. However, concession agreements and market conditions often also pressure terminals to compete. This paper aims to help understand how pressures for competition and cooperation conflict, what problems this causes, what drives these tensions, and how these can be resolved. The drivers of port competitiveness are generally conceptualized as straightforward criteria related to costs, efficiency, location, and infrastructure. Because of the focus on these 'hard', quantifiable factors, the qualitative relational underpinnings of port performance are often overlooked. This paper explores how inter-organizational relations function as a major underpinning of port performance and competitiveness. Interviews with a representative selection of stakeholders in the Port of Rotterdam reveal the problems that can occur when cooperation between terminals is under pressure. These problems relate to deficiencies in inter-organizational relationships, which do not tend to arise spontaneously in a competitive context. This paper provides a framework that helps understand how firms can simultaneously balance pressures for competition and imperatives for cross-firm integration and cooperation. Several technical and organizational solutions are suggested, but effective implementation depends on various tacit factors - including trust, shared values, and a sense of community - that determine stakeholders' willingness to commit and cooperate.
Keywords: 650; Ports; Port governance; Container terminals; Container transport; Inter-organizational relations; Intra-port competition